Implementasi Taksonomi Bloom Pemahaman Dokumen Perpajakan Terhadap Hasil Belajar Dimoderasi Motivasi Belajar - Reni Hariyani; Fenti Sofiani (Akademi Sekretari Budi Luhur, 2020)
This research aims to determine significantly the implementation of Bloom's Taxonomy and understanding of tax documents that affect the learning outcomes of Tax Administration course with learning motivation as a moderating variable. The population of this study was students of Akademi Sekretari Budi Luhur Year 2019/2020 for the Class of 2018. The sample taken using purposive sampling method amounted to 46 students. The research methods are quantitative and qualitative. Data analysis using SPSS Version 22 software uses 2 models, namely multiple regression analysis and regression analysis with moderating variables. The results of the study, namely the implementation of Bloom's Taxonomy do not significantly affect student learning outcomes in the Tax Administration course, because Diploma 3 students according to the rank at level 5 listed in the KKNI (Indonesian National Qualifications Framework) have the ability to Bloom’s Taxonomy levels at the level of knowledge and understanding. This means that students have not been able to have cognitive thinking skills up to the level of application, analysis, synthesis, and evaluation. Understanding of taxation documents does not significantly affect student learning outcomes in the Tax Administration course, because tax documents are only theoretical material in the RPS (Semester Learning Plan) with total 10% of the overall material. Meanwhile, the majority of the material is the practice of calculating in the form of numbers. The results of research for learning motivation can moderate the implementation of Bloom's Taxonomy and understanding of tax documents on student learning outcomes in the Tax Administration subject with an increase in the R square value of 9.5%. Keywords: implementation of Bloom’s Taxonomy, understanding of taxation documents, learning outcome, learning motivation